Gli “effetti secondari” (ma non troppo) della pandemia sul diritto ecclesiastico italiano e le sue fonti (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Un contrasto “accademico” - 2. Sulla possibilità di porre restrizioni all’effettivo esercizio delle libertà democratiche garantite dalla Costituzione: condizioni e limiti - 3. La necessità del ricorso al principio e al test di proporzionalità - 4. L’occasione mancata di un proficuo confronto - 5. Gli effetti secondari (ma non troppo) della pandemia: “fratture” e “passaggi” - 6. Alla declinante bilateralità in senso stretto si affianca la concertazione in ascesa: prospettive e vuoti – 7. I rischi della bilateralità “diffusa” – 8. Un cenno finale.The "secondary” (yet not unimportant) effects of the pandemic on the Italian law and religion and its sources.The author explains the reasons why the limitations of freedom of worship have been an issue of secondary interest to him during the pandemic. He stresses how the topic should be examined indipendently, as the limitations have affected all the democratic freedoms. The pandemic has made it clear that religious freedom cannot be considered as a “special right”. As other foundamental rights, this should also be subject to reasonable accommodation. The pandemic has also allowed the scholars to consider using new types of administrative arrangements to replace the “classic” agreements between the State and the religious organisations (“concordati” and “intese”).